2017
DOI: 10.4236/jfrm.2017.61005
|View full text |Cite
|
Sign up to set email alerts
|

Credit Risk Management Framework for Rural Commercial Banks in China

Abstract: Credit risk management (CRM) is to identify, measure, monitor, and control risk arising from the possibility of default in payments. Existing CRM tools available for large financial institutions do not meet the requirements of rural commercial banks (RCBs) because their main customers are SMEs and farming households whose financial data and credit rating records are not available. RCBs in China also expose specific risks connected to rural commercial banking business and in particular farming-related loans and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Moreover, more bad loans lead to higher provision which can impact the bank performance because the provision is generated from prot. Then, the bank will get higher nancial leverage which can cause nancial bubbles of bank's credit risk [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, more bad loans lead to higher provision which can impact the bank performance because the provision is generated from prot. Then, the bank will get higher nancial leverage which can cause nancial bubbles of bank's credit risk [29].…”
Section: Resultsmentioning
confidence: 99%
“…According to Berger and DeYoung (1997) [28], the increase in nonperforming loans is due to the weakness in the credit appraisal process before, during, and after lending, leading to the bank's wrong choice of lending customers (customers not eligible for loans). According to Wang et al (2017) [29], the credit risk also occurs when the weak professional competence of employees in properly assessing the value of collaterals, businesses, and individual customers those are unqualied.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the relevant research in developed countries can be very important reference point for the credit risk assessment of Chinese commercial banks, but this kind of reference should not be copied without question. (Wang, et al, 2017). Meanwhile, in response to the revision of foreign risk measurement models, Wu, Liu, and Huang (2010) suggested that the banks should consider data adoption, credit rating and market environment and human resources.…”
Section: Resultsmentioning
confidence: 99%
“…Banks in rural areas have short development times, with obvious geographical restrictions, and encounter challenges of backward information technology, such as a lack of high-speed wireless networks, big data, and cloud computing facilities. The strategies of credit risk management and services of online banking have also been shown to be lacking in RCBs [55]. Thus, an obvious technology gap exists between RCBs and other banks.…”
Section: The Lerner Index (Li) and Scale Economies (Sc)mentioning
confidence: 99%